Characterizing the Electroluminescence Emission from a Strongly Coupled Organic Semiconductor Microcavity LED. Issue 7 (28th May 2013) - Christogiannis, Nikolaos; Somaschi, Niccolo; Michetti, Paolo; Coles, David M.; Savvidis, Pavlos G.; Lagoudakis, Pavlos G.; Lidzey, David G.
<x xml:space="preserve">Abstract</x> The fabrication of a strongly coupled organic semiconductor light emitting diode (OLED) is described. The device is characterised through angle‐resolved photoluminescence and electroluminescence spectroscopy, with the efficiency of the polariton OLED being compared to that of an equivalent weakly coupled device. The external emission efficiency of the polariton OLED is approximately 6 times smaller than that of the OLED; an effect that is attributed to the relatively slow scattering of excitons towards states at the bottom of the lower polariton branch. The temporal responses of the polariton and standard OLED devices are measured under pulsed voltage excitation, and device dynamics are found to be limited by charge transport and recombination.